Content-based image retrieval system (CBIR System) - Cathy, Stanislaus Saili; Elaine, Tang Wei Wei; Soo, Siow Wei (Universiti Malaysia Sarawak (UNIMAS), 2004)
We witnessed the important role of images as the information keeper and communications giver in life. As image technology evolved, image database have become very popular and been used in various applications. This requires effective and efficient image retrieval systems to access the image database based on the images' feature such as shape, texture and color. The Content-based Image Retrieval system (CBIR) can use many more features and it is the key solution in utilizing information from image database. This project aims to develop a working prototype system, which includes image manipulation functions where color-based image retrieval will be used. It is clarified that there are four important issues to achieve this color-based image retrieval project which led to results of retrieving perceptually similar images: [a] what color-space used to describe, analyze and compare image; [b] how to represent the image descriptions in an image database; [c] what approach been used in measuring the image similarity based on color-feature and [d] what access method used to index the color features. For further works, this project can be enhanced and extended to more advance content-based image retrieval system and applications